Marination of fish in advance - Mumbai Archive Project Team (Jio Institute, 2024)
Marinating fish in advance saves time during busy meal times and allows the flavours to develop over time. The marinade infuses the fish with additional layers of flavour, creating a more complex and delicious taste profile.